Assessment of the Lubricity of Grease‐Sealing Rotary Shaft Seals Based on Grease Properties. Issue 1 (17th October 2022) - Hahn, Susanne; Feldmeth, Simon; Bauer, Frank
Abstract: Grease‐lubricated sealing systems have an increased risk of starved lubrication. For this work, the lubricity of 23 greases in a rotary shaft sealing system was evaluated with a new test and evaluation method. The lubricity was then correlated with rheological and other grease properties. These grease properties are either available by the data sheet or can be measured with low effort. The results of the correlation allow a preselection of greases which are expected to lubricate rotary shaft seals well. This can support manufacturers and users in considering the lubrication of the sealing system early in the development process. Abstract : Grease‐lubricated rotary shaft sealing systems have an increased risk of starved lubrication. For this work, the lubricity of 23 greases was first evaluated and then correlated with grease properties. The results show which properties correlate with the lubricity of the greases and how the lubricity of the grease can be predicted on the basis of short rheological tests or already available data.